Improvement Management at MI Tarbiyah Islamiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The quality of basic education is one of the benchmarks for the success of the national education system, including in the madrasah ibtidaiyah environment as an Islamic-based educational institution. This study aims to describe and analyze the quality improvement management strategy implemented at MI Tarbiyah Islamiyah, as well as to identify supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach with data collection techniques through observation, documentation studies, and in-depth interviews with key informants involved in madrasah management. The results of the study indicate that MI Tarbiyah Islamiyah implements a participatory quality planning strategy, implements internal teacher competency improvement programs, and carries out reflective and collaborative supervision and evaluation. The active involvement of stakeholders, such as the madrasah committee and parents of students, is one of the main strengths in supporting the sustainability of the quality program. However, there are still challenges in terms of technology integration, evaluation documentation, and strengthening data-based managerial systems. This study concludes that the success of quality improvement management is greatly influenced by madrasah leadership, internal collaboration, and commitment to continuous improvement.